A Consideration for Surgical Management in Select T4b Oral Cavity Squamous Cell Carcinoma. (June 2022) - Chen, Michelle M.; Chang, Clifford M.; Dermody, Sarah; Rosko, Andrew J.; Mierzwa, Michelle L.; Swiecicki, Paul L.; Spector, Matthew E.; Worden, Francis P.; Prince, Mark E. P.; Chinn, Steven B.
Objectives: The role of surgery for conventionally "unresectable" (cT4b) oral cavity squamous cell carcinoma is unclear. We analyzed factors associated with overall survival in cT4b relative to cT4a oral cavity squamous cell carcinoma. Methods: We identified 6830 cT4a and 522 cT4b oral cavity squamous cell carcinoma chemoradiation or surgery + adjuvant therapy patients in the National Cancer Data Base from 2004 to 2016. The main outcome was overall survival. Statistical analysis was performed using chi-squared tests, univariable and multivariable regression analysis. Results: The cT4b group had a higher rate of positive margins (30.4% vs 21.3%, P = .009) and downstaging (41.2% vs 13.1%; P < .001) compared to cT4a, while only 1.7% were upstaged. cT4b surgery + chemoradiation patients had similar survival to cT4a surgery + radiation (HR 0.93; 95% CI, 0.70-1.25) and cT4a surgery + chemoradiation patients (HR, 0.92; 95% CI, 0.69-1.23), while cT4b surgery + radiation patients had worse OS (HR, 1.55; 95% CI, 1.05-1.47). Conclusions: Clinical T4b staging is a poor predictor of pathologic staging given a high rate of downstaging on final pathology. Surgical resection with adjuvant chemoradiation is an option in select cT4b oral cavity squamous cell carcinoma patients.